Combining small-sided soccer games and running-based methods: A systematic review - Clemente, F.; Sarmento, H. (Biology of Sport, 2021)
Small-sided games (SSGs) are often used in soccer to produce acute physiological and physical responses, while a tactical/technical stimulus is also employed. However, due to some limitations of SSGs, researchers have been testing this method combined with running-based training methods. This systematic review was conducted to assess the effects of combined SSG and running-based methods on soccer players` acute responses and adaptations after training interventions. A systematic review of Web of Science, PubMed, Cochrane Library, Scopus, and SPORTDiscus databases was performed according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. The database search initially identified 782 titles. From those, five articles were deemed eligible for the systematic review. The five included studies presented data from training load, reporting inconsistent greater values in combined SSG and running-based methods when compared to SSG-only formats. Considering the adaptations, studies comparing combined SSG and running-based methods with SSG-only methods revealed inconsistent differences in terms of the effects on aerobic performance and sprinting. Combining SSG and running-based methodscan increase the acute mechanical load and high-intense running stimuli in players when compared to interventions that use only SSGs. However, the adaptations promoted by both methods are similar, and the differences are unclear. The order of combination (SSG and running-based method) does not seem to impact players` adaptations; however, the frequency of sessions did have a meaningful impact.